2013
DOI: 10.5935/abc.20130129
|View full text |Cite
|
Sign up to set email alerts
|

ALK7 Gene Polymorphism is Associated with Metabolic Syndrome Risk and Cardiovascular Remodeling

Abstract: BackgroundActivin receptor-like kinase 7 (ALK7) is a type I receptor for the TGF-β superfamily and has recently been demonstrated to play an important role in the maintenance of metabolic homeostasis. ObjectiveTo investigate the association of the ALK7 gene polymorphism with metabolic syndrome (MetS) and cardiovascular remodeling in MetS patients. MethodsThe single nucleotide polymorphism rs13010956 in the ALK7 gene was genotyped in 351 Chinese subjects undergoing carotid and cardiac ultrasonography. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The signaling pathway mediated by ALK7 plays an important role in cell apoptosis, proliferation, and tissue development, and is involved in neuromuscular diseases, endocrine disorders, obesity, tumors, and other diseases. ALK7-related signaling pathways have some important regulatory effects on the body [ 9 11 ]. High level of ALK7 is observed in breast cancer tissues and ALK7 overexpression inhibited cell growth and adhesion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The signaling pathway mediated by ALK7 plays an important role in cell apoptosis, proliferation, and tissue development, and is involved in neuromuscular diseases, endocrine disorders, obesity, tumors, and other diseases. ALK7-related signaling pathways have some important regulatory effects on the body [ 9 11 ]. High level of ALK7 is observed in breast cancer tissues and ALK7 overexpression inhibited cell growth and adhesion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cloud computing is widely used in big data science. It has gradually entered the mature stage from the primary stage [1] . And it is getting wider and wider in terms of application scope.…”
Section: Current Status Of Cloud Computing In Big Data Sciencementioning
confidence: 99%
“…It has been reported that deficiency of TLR4 affects doxorubicin-induced cardiomyopathy in mice [14]. Aberrant expression or genetic polymorphisms is recognized as a risk factor for metabolic syndrome and is associated with cardiovascular remodeling [15]. Kiechl et al have reported that TLR4 polymorphisms are associated with heart disease, such as atherogenesis [16].…”
Section: Introductionmentioning
confidence: 99%